2021
DOI: 10.3390/biom11121784
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intestinal Alkaline Phosphatase in Innate Immunity

Abstract: Intestinal alkaline phosphatase (IAP) is a multi-functional protein that has been demonstrated to primarily protect the gut. The role of IAP in maintaining intestinal homeostasis is underscored by the observation that IAP expression is defective in many gastrointestinal-related disorders such as inflammatory bowel disease IBD, necrotizing enterocolitis, and metabolic syndrome and that exogenous IAP supplementation improves the outcomes associated with these disorders. Additionally, studies using transgenic IAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…IAP has been found mediating interactions between microorganism communities and the host. IAP dephosphorylates LPS and other pathogen-associated molecular patterns, reducing local intestinal inflammation [ 35 ] and helping maintain gut barrier function [ 29 , 36 ]. IAP supplementation has been reported to be able to ameliorate experimental colitis [ 37 ], reverse metabolic syndrome [ 38 ], prevent liver fibrosis [ 21 ], and attenuate alcohol-induced hepatosteatosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…IAP has been found mediating interactions between microorganism communities and the host. IAP dephosphorylates LPS and other pathogen-associated molecular patterns, reducing local intestinal inflammation [ 35 ] and helping maintain gut barrier function [ 29 , 36 ]. IAP supplementation has been reported to be able to ameliorate experimental colitis [ 37 ], reverse metabolic syndrome [ 38 ], prevent liver fibrosis [ 21 ], and attenuate alcohol-induced hepatosteatosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the activity of ACP showed an increased trend in the coelom with a peak at 48 hpi, while it exhibited a decreased pattern except a significant elevation at 48 hpi, suggesting ACP in polian vesicle had a slight and delayed response to pathogenic infection. AKP has been demonstrated to play a role in innate immune response by lipopolysaccharide (LPS) detoxification, anti-inflammatory function and induction of autophagy in many studies [ 35 , 36 ]. In our result, the AKP activity both in the coelomic and polian vesicle fluid shared a consistently increasing levels after V. splendidus challenge, revealing an important role of AKP in coelomic and polian vesicle fluid.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the IAP enhancer could still reach the duodenum after it was exposed to gastric acid. IAP dephosphorylates LPS ( 60 ), ATP ( 11 ), and UDP ( 61 ). However, the effect of IAP on dephosphorylation has not been reported in the pH range (pH 5–8) in the small intestine of humans and other nucleoside triphosphates.…”
Section: Discussionmentioning
confidence: 99%